The role of Glu N1 activated nitric oxide synthase in rat model of post traumatic stress disorder - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (My University, 2016)
Objectives: Activation of neuronal nitric oxide synthase (nNOS) and interrelated alterations of calmodulin and ionotropic glutamate receptor (GluN1) levels are unknown in post traumatic stress disorder (PTSD). Materials and Methods: Sprague-Dawley rats of both sexes were exposed to to dirty cat litter, and then placed on an elevated plus maze. An anxiety index was calculated and tissue samples from hippocampus and amygdala were prepered in order to to detect calmodulin, NOS and GluN1 by immunoblotting. Results: The anxiety indices of the traumatized rats were markedly higher than those of the controls (p<0.05). GluN1 and calmodulin levels were decreased in the dorsal hippocampus and amygdaloid complex of the traumatized rats. NOS expression increased significantly in both the amygdaloid complex and dorsal hippocampus where the increase was statistically more prominent in the amygdaloid complex (p< 0.001) than in the dorsal hippocampus of the traumatized rats (p<0.05). Conclusion: Predator exposure in rats causes long-lasting anxiogenic effects associated with increases in NOS and decreases in GluN1 expressions in brain areas related to PTSD symptoms and excitotoxicity. The results suggest that excitotoxicity occurs through other mechanisms rather than GluN1 receptors. Keywords: Predator scent test, nNOS, Glutamate, Calmodulin, Amygdala, Hippocampus

Amaç: Post travmatik stres bozukluğunda (PTSD) iyonotropik glutamat reseptör (GluN1)’lerinin (GluN1) ve kalmodülinin birlikte etki ederek nitrik asit sentaz (NOS) aktivasyonu yaptığı bilinmemektedir. Gereç ve Yöntem: Her iki cinsiyetten Sprague-Dawley sıçanları kirli kedi kumuyla saldırgan hayvan kokusuna maruz bırakıldıktan sonra, sıçanlara yükseltilmiş t labirenti deneyleri uygulanmıştır. Deney sonrası sıçanların anksiyete endeksleri hesaplanmış ve kalmodülin, NOS ve GluN1 ölçümleri için hipokampüs ve amigdala doku örnekleri Western Blot yöntemi için hazırlanmıştır. Bulgular: Travmatize edilen sıçanların anksiyete indeksleri kontrol grubuna göre anlamlı olarak yüksek bulunmuştur (p < 0.05). Dorsal hipokampüs ve amygdaloid komplekste travmatize sıçanların GluN1 ve kalmodülin düzeyleri azalmıştır. NOS ekspresyonu her iki bölgede artış göstermesine karşın, amigdaloid kompleksteki artış (p < 0.001) dorsal hipokampüse göre (p < 0.05) istatiksel olarak daha anlamlı bulunmuştur. Sonuç: Saldırgan hayvan kokusu maruziyeti sıçanlarda, PTSD semptomları ve eksitotoksisite ile ilişkili beyin alanlarında nNOS ekspresyonunda artma ve GluN1 reseptörlerinde azalma ile birlikte uzun süre devam eden anksiyete ilişkili etkilere neden olmaktadır. Sonuçlarımız, NOS aktivitesinin GluN1 dışındaki nedenlerle arttığını göstermektedir. Anahtar kelimeler: Saldırgan hayvan kokusu testi, nNOS, Glutamat, Kalmodülin, Amigdala, Hipokampüs
Post travmatik stres bozukluğu sıçan modelinde GluN1 ile aktiflenmiş nitrik oksit sentetazın rolü
Keywords: Predator scent test; nNOS; Glutamate; Calmodulin; Amygdala; Hippocampus; Saldırgan hayvan kokusu testi; Glutamat; Kalmodülin; Amigdala; Hipokampüs